Peningkatan Pembelajaran Permainan Bola Kecil Melalui Permainan Tradisional Gaprek Kempung (Department of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this study was to determine the improvement of learning and learning outcomes through thesmall ball game Gaprek Kempung traditional games for 5th graders Purwoyoso State Elementary School 03years 2013/2014. The method of research is a class act. Based on the results obtained by observations for theactivity of students has increased from the first cycle and second cycle. Increased activity of student learning isnot separated from the reflection of the results of student learning activities in cycle I. Results of reflection on the first cycle also affects the increase of the test results on the second cycle. Thoroughness evident from students in the first cycle is 81% and the second cycle increased to 100%. Based on these results it can be concluded that the application of traditional games Gaprek Kempung in the process of learning the game of small ball can improve the learning process and improve learning outcomes fifth grade students of State Elementary School 03 Semarang Purwoyoso academic year 2013/2014.